A molecular, morphological and cytological investigation of the identity of non-native Ludwigia (Onagraceae) populations in Britain. (August 2013) - Armitage, J D; Könyves, K; Bailey, J P; David, J C; Culham, A
Abstract : A combined molecular, morphological and cytological analysis was used to study the identity and number of species of Ludwigia section Oligospermum occurring in British waterways. Only one taxon was identified for which the name L. grandiflora subsp. hexapetala (Hook. & Arn.) G.L. Nesom & Kartesz is preferred. A chromosome count of 2 n = 80 was made for all plants tested and DNA evidence demonstrates that at least two clones are present in Britain. Morphological characters to differentiate L.grandiflora subsp. hexapetala and L. peploides subsp. montevidensis (Spreng.) P.H. Raven are provided. Though the production of fruit in Britain by apparently isolated populations is noted, repeated introduction into the wild from gardens is judged to be primarily responsible for the British distribution of the taxon. Legislative implications are considered and an amendment to Schedule 9 of the UK Wildlife and Countryside Act (1981) is strongly advocated.